Whether the Unilateral Transverse Process-pedicle Approach has Advantages over the Traditional Transpedicle Approach: A Systematic review and Meta-analysis - Wang, Lingbin; Zhu, Linfeng; Li, Junjie (Zeitschrift für Orthopädie und Unfallchirurgie, 2022)
Purpose To summarize the literature and compare the advantages and disadvantages of the unilateral transverse process-pedicle approach (UTPA) and conventional transpedicular approach (CTPA) vertebral augmentation in the treatment of osteoporotic vertebral compression fractures (OVCF).Methods A single researcher performed a systematic literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Online scientific databases were searched in September 2021 for English- and Chinese-language publications. A series of comparative studies were included, with UTPA as the main intervention and CTPA as the comparison indicator. A meta-analysis was performed for studies that reported clinical outcome indicators. The χ2 was used to study heterogeneity between trials, and the I2 statistic was calculated to estimate variation across studies.Results A total of eight studies were included for meta-analysis, all of which were observational studies with mixed bias risk. There were 613 subjects in the UTPA group and 488 subjects in the CTPA group. The results of the meta-analysis showed that there was no difference between the UTPA group and the CTPA group in terms of visual analogue scale scores (p = 0.31), Oswestry Disability Index scores (p = 0.50), correction of kyphosis angle (p = 0.65), and the amount of bone cement (p = 0.13), but the UTPA group had a shorter operative time (p < 0.001), bone cement leakage rates (p = 0.02), and fluoroscopy times than the CTPA group (p < 0.001). Partial analysis results had a high risk of bias, and the most common source of bias was that there was high heterogeneity between studies, and the sensitivity can only be reduced by a random effect model, and some studies (four items) did not clearly describe the confounders that they controlled.Conclusion The limited evidence obtained in this study proves that the new puncture method does not have more advantages than the traditional technique, so it is no longer meaningful to continue to obsess over the impact of the puncture method on surgical outcome.
Keywords: unilateral transverse process-pedicle approach; vertebral augmentation; osteoporotic vertebral compression fractures; Systematic review; meta-analysis